Muscle injuries in sports: A new evidence-informed and expert consensus-based classification with clinical application - Valle, X.; Alentorn-Geli, E.; Tol, J. L.; Hamilton, B.; Garrett, W. E.; Pruna, R.; Til, L.; Gutierrez, J. A.; Alomar, X.; Balius, R.; Malliaropoulos, N.; Monllau, J. C.; et al. (Sports Medicine, 2017)
Muscle injuries are among the most common injuries in sport and continue to be a major concern because of training and competition time loss, challenging decision making regarding treatment and return to sport, and a relatively high recurrence rate. An adequate classification of muscle injury is essential for a full understanding of the injury and to optimize its management and return-to-play process. The ongoing failure to establish a classification system with broad acceptance has resulted from factors such as limited clinical applicability, and the inclusion of subjective findings and ambiguous terminology. The purpose of this article was to describe a classification system for muscle injuries with easy clinical application, adequate grouping of injuries with similar functional impairment, and potential prognostic value. This evidence-informed and expert consensus-based classification system for muscle injuries is based on a four-letter initialism system: MLG-R, respectively referring to the mechanism of injury (M), location of injury (L), grading of severity (G), and number of muscle re-injuries (R). The goal of the classification is to enhance communication between healthcare and sports-related professionals and facilitate rehabilitation and return-to-play decision making.